2013
DOI: 10.1186/2251-7456-7-37
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of bi-invariant Finsler metrics on Lie groups

Abstract: In this paper, we prove some common fixed point results for four mappings satisfying generalized contractive condition in S-metric space. Our results extend and improve several previous works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The bi-invariance means the geometry is both right and left invariant. It has been shown that, in bi-invariant Finsler geometry, the curve c(s) is a geodesic if and only if there is a constant generator H(s) =H such that [34,35] c(s) =Hc(s) or c(s) = exp(sH) . The minimization 'min' in (3.9) in the sense of 'geodesic' is already taken care of in (5.9).…”
Section: Geodesics and Complexity Of Su(n) Operatorsmentioning
confidence: 99%
“…The bi-invariance means the geometry is both right and left invariant. It has been shown that, in bi-invariant Finsler geometry, the curve c(s) is a geodesic if and only if there is a constant generator H(s) =H such that [34,35] c(s) =Hc(s) or c(s) = exp(sH) . The minimization 'min' in (3.9) in the sense of 'geodesic' is already taken care of in (5.9).…”
Section: Geodesics and Complexity Of Su(n) Operatorsmentioning
confidence: 99%
“…(2.10). It has been shown in Refs [58,59]. that, if the Finsler metric is bi-invariant, the curve c(s) is a geodesic if and only if there is a constant generator H(s) =H such thatċ (s) =Hc(s) or c(s) = exp(sH) .…”
mentioning
confidence: 99%
“…10). It has been shown that, in bi-invariant Finsler geometry, the curve c(s) is a geodesic if and only if there is a constant generator H(s) =H such that[58,59] c(s) =Hc(s) or c(s) = exp(sH) . (5.13) With the boundary conditionÔ = c(1) = exp(H),H = lnÔ, which is the same as Ref.…”
mentioning
confidence: 99%
“…Bi-invariant Finsler functions on Lie groups have been extensively investigated in the literature (see e.g. [9,6]). However, explicit examples for such functions -that are non-Riemannianare rarely calculated.…”
Section: Introductionmentioning
confidence: 99%